Feeling bad can be good?: audience research on Korean reality makeover shows, Get It Beauty and The Body Show - Lee, Jin; Lee, Claire S (Taylor & Francis, 2017)
This paper investigates the feelings of individuals who have been exposed to the continuous demands for managing and beautifying the body. Through audience research on Korean reality shows about body/beauty, Get It Beauty and The Body Show, we attempt to understand how the discourses of body care work at the individual level. Our interviewees’ feelings of being stressed, burdened, and annoyed about the discourses in the shows signify their (un)conscious acknowledgment of the false promises of the self-care rhetoric. However, the discourses of willpower and the embedded voyeuristic pleasure of watching the shows make it difficult to place such feelings in the public domain. We conclude that individuals’ feelings lose their potential as resistant voices when “feeling bad” is discounted as personal, while a feeling of individual achievement is excessively celebrated.